2012
DOI: 10.1080/02786826.2012.667585
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Diffusion Charging of Aggregates

Abstract: In this paper, the effect of particle morphology on bipolar diffusion charging is studied. A modified tandem differential mobility analyzer (TDMA) method used to measure the charge distribution of submicron particles in the range of 70-300 nm is described in detail. The method requires an independent measurement of the neutral fraction, followed by the measurement of the size-dependent charge distribution, which requires the knowledge of the neutral fraction. The method was validated experimentally using dioct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(39 reference statements)
0
7
1
Order By: Relevance
“…The experimental data from Maricq (2008) suggested that the regression fit by Wiedensohler (1988) reproduce the ratios of the positively double to single charged particles within §12% for neutralized soot particles produced in a premixed ethylene flame. On the other hand, the experimental results of Xiao et al (2012) for neutralized diesel soot particles, suggested that the ratios of double to single positively charged particles are underestimated by approximately 20% by the regression fit of Wiedensohler (1988). Table 2 compares the results determined for particles produced by the miniCAST (Soot #1 condition) when employing 85 Kr and X-ray sources in the second neutralizer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental data from Maricq (2008) suggested that the regression fit by Wiedensohler (1988) reproduce the ratios of the positively double to single charged particles within §12% for neutralized soot particles produced in a premixed ethylene flame. On the other hand, the experimental results of Xiao et al (2012) for neutralized diesel soot particles, suggested that the ratios of double to single positively charged particles are underestimated by approximately 20% by the regression fit of Wiedensohler (1988). Table 2 compares the results determined for particles produced by the miniCAST (Soot #1 condition) when employing 85 Kr and X-ray sources in the second neutralizer.…”
Section: Resultsmentioning
confidence: 99%
“…Inaccuracies in the assumed charged fractions is one of the main contributors of the measurement uncertainties of such spectrometers (Liu and Deshler 2003) and can have a strong effect on the recovered number concentrations (Xiao et al 2012). Any progress in the understanding of charging mechanisms can help improve the quality of DMA size distribution measurements (Gopalakrishnan et al 2015), especially since experimental quantification of charging probabilities would be impractical in such applications.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al (2012) found that compact diesel agglomerates with d m D 70-300 nm, which are more compact than the chain aggregates used in Lall and Friedlander's (2006) theory, can show the electrical charging behavior similar to spherical particles.…”
Section: Introductionmentioning
confidence: 94%
“…For correction the bipolar charge distribution of the agglomerates has to be known. This information is still limited (Rogak and Flagan, 1992;Maricq, 2008;Xiao et al, 2012). Lall et al (2006a, b) used a model for bipolar agglomerate charging developed by Wen et al (1984a, b) approximating agglomerate structure by long prolate spheroids.…”
Section: Existing Technologies and Data Evaluation Proceduresmentioning
confidence: 99%
“…To perform the correction for agglomerates/aggregates similar to what is done with spherical particles one needs the bipolar charge distributions of agglomerates/aggregates as function of mobility diameter for any kind of structure. Unfortunately the information about these distributions in form of measurements and models is limited (Wen et al, 1984a, b;Rogak and Flagan, 1992;Maricq, 2008;Xiao et al, 2012) To demonstrate the procedure and to discuss the importance of the correction we use the limited model for chain like agglomerates by Wen et al (1984a, b). With the known charge distribution Eq.…”
Section: Determination Of Number Concentration Distribution As Functimentioning
confidence: 99%